Effects of Copper, Zinc, and Vitamin Complex (Cernevit®) on Hepatic Healing in Rats Experimentally Subjected to Blunt Hepatic Trauma - Ayten, Refik; Aygen, Erhan; Cerrahoglu, Yusuf Ziya; Camci, Cemalettin; Ilhan, Yavuz Selim; Girgin, Mustafa; Ozercan, Ibrahim Hanefi (Springer India, 2015)
Solid organ injuries following blunt trauma are frequently encountered. The use of non-operative approach is gradually increasing. Thus, research on the methods that could enhance healing in solid organ injuries is in progress. Agents known to have antioxidant property were used after an experimentally induced blunt hepatic trauma. Thirty-two Wistar albino rats weighing 200 g were dropped from a height of 40 cm on to the right upper abdominal quadrant to produce a grade II-III hepatic injury. Rats were divided into control, Zn-administered, Cu-administered, and vitamin complex-administered groups, with eight rats in each. Aminotransferase (AST), alanine aminotransferase (ALT), and lactate dehydrogenase (LDH) levels were measured in the blood samples. The percentage of cells displaying Ki-67 nuclear staining was estimated. The sections were stained with hematoxylin and eosin and the degree of inflammation in the samples was semi-quantitatively assessed. Treatment with zinc, copper, and Cernevit (R) caused varying levels of decrease in AST, ALT, and LDH levels compared to the control group. Ki-67 positivity was significantly lower in group I compared with groups II and III (p=0.002). Ki-67 positivity was significantly higher in group II compared to the other groups (p<0.05). A marked improvement was observed in inflammation in group II. Copper and zinc treatment decreased inflammation as well as blood levels of AST and ALT, and enhanced the healing of traumatized hepatic tissue. However, Cernevit (R) reduced only the degree of inflammation.
Keywords: Blunt hepatic trauma; Cooper; Zinc; Vitamin complex; Hepatic healing